The Hong Kong Umbrella Movement as a non‐profit organization: An empirical study on the use of visual branding practices for social change. Issue 2 (2nd July 2021) - Patsiaouras, Georgios; Veneti, Anastasia; Green, William
Abstract: In this article, we draw our attention to the growth of a new social movement, as a non‐profit organization which aims to effectively communicate its collective identity and messages to larger audiences. Initially, we provide a critical discussion on the interrelationships between marketing theory/practice and protest groups' promotional tactics. Afterwards, we focus on the interface between visual branding practices and new social movement's strategies to create a visual branding identity around their protest symbols and aims. In order to do so, we adopted a moderate participant observation approach to explore how the 2014 Hong Kong Umbrella Movement employed forms of visual branding to engage local and global audiences and induce social change. Drawing on a close examination of field notes and a visual analysis of digital archives and images from the protest sites, we identify and discuss the presence of several visual branding techniques for the imaginative promotion of the movement's demands and causes. Our findings suggest that the 2014 Umbrella Movement protesters coordinated and acted as non‐profit organization which employed innovative and creative visual branding methods to enhance the movement's unity and trigger emotional responses from diverse audiences. We conclude the article with suggestions for future research around the interrelationships between social movements' protest symbols, transnational visual branding practices and non‐profit organizational practices.